The efficacy of 5-ASA preparations in prevention of postoperative recurrence of Crohn’s disease (Retrospective assesstment) - Erkan PARLAK,; Aysel ÜLKER,; Canan ALKIM,; Bilge TUNÇ,; Ahmet TEZEL,; Ülkü DAĞLI, (Turkish Journal of Gastroenterology, 2019)
-